PROCESS MODEL OF OPERATION PROBLEM HANDLING IN DIFFERENTIATED SERVICES SYSTEMS WITH GUARANTEED SERVICE - Луцький, М. Г.; Муранов, А. С.; Муранов, О. С. (Science-based technologies, 2010)
In keeping with DSTU ISO 9001 requirements, a process approach is proposed to creation of an operation problem handling model, which is intended for use in network services systems within the infrastructure of corporate computer networks at airports. This model provides a possibility of differentiated service for client applications, together with corresponding guarantees of high-quality service. The model is built on the basis of the concept of so called TOM-model of MCE-T supported telecommunication network administration structure. Service processes have been structured and correlation has been established among both the processes and the services, operating corporate computer networks at airports, which support these processes. The processes and their correlation are represented by graphs, whose interconnected clusters represent the developed model.